Dual sensory impairment in special schools in South-Eastern Nigeria. Issue 2 (18th January 2017) - Aghaji, Ada E; Bowman, Richard; Ofoegbu, Vincent C; Smith, Andrew
Abstract : In a cross-sectional study to determine the magnitude of dual sensory impairment (DSI-combined hearing and vision loss) in children in single-disability special education schools, children in schools for the blind and schools for the deaf in four states in South-East Nigeria were examined by an ophthalmologist and otorhinolaryngologist to determine the level of their disability and to identify other disabilities if any. Participants were all students with childhood blindness or childhood deafness. The magnitude and causes of DSI and the burden of undetected DSI were the main outcome measures. A total of 273 students were examined. About 7% of these students had DSI out of which over 60% (12/19) was previously undetected. There was more DSI in the blind schools than in the deaf schools (p=0.003). There is a large burden of undetected DSI in children in special schools in Nigeria. There is a need to create awareness of this problem and advocate appropriate screening, rehabilitative and educational strategies for children who have it.